THE METHODOLOGY OF INCREASING THE MASTERY LEVELS OF STUDENTS’ UNDERSTANDING OF ROTATION OF SOLID BODIES - Irmatov, Fozil Muminovich (Innovative Development in Educational Activities, 2023)
This article the main focus in the teaching of physics to students is the content of theoretical materials necessary for the formation of scientific thinking among students, the creation of opportunities for independent study of physics.